Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Sure, let's solve the given quadratic equation step by step. The equation we have is:
[tex]\[ y = x^2 - 5x - 14 \][/tex]
### Step 1: Factoring the quadratic expression
To factor the quadratic expression [tex]\( x^2 - 5x - 14 \)[/tex], we need to find two numbers that multiply to [tex]\(-14\)[/tex] (the constant term) and add up to [tex]\(-5\)[/tex] (the coefficient of [tex]\(x\)[/tex]).
List the pairs of factors of [tex]\(-14\)[/tex]:
- [tex]\((-1, 14)\)[/tex]
- [tex]\((1, -14)\)[/tex]
- [tex]\((2, -7)\)[/tex]
- [tex]\((-2, 7)\)[/tex]
Among these pairs, we need to find the one that adds up to [tex]\(-5\)[/tex]:
- [tex]\((-1) + 14 = 13\)[/tex]
- [tex]\( 1 + (-14) = -13\)[/tex]
- [tex]\( 2 + (-7) = -5\)[/tex]
- [tex]\((-2) + 7 = 5\)[/tex]
The pair [tex]\((2, -7)\)[/tex] adds up to [tex]\(-5\)[/tex], which is what we need.
### Step 2: Writing the equation in factored form
Now that we have found the pair of numbers [tex]\(2\)[/tex] and [tex]\(-7\)[/tex], we write the quadratic equation in its factored form:
[tex]\[ y = (x + 2)(x - 7) \][/tex]
### Step 3: Finding the zeros/solutions of the equation
To find the zeros or [tex]\(x\)[/tex]-intercepts of the equation, we set each factor equal to zero and solve for [tex]\(x\)[/tex]:
1. [tex]\( x + 2 = 0 \)[/tex]
[tex]\[ x = -2 \][/tex]
2. [tex]\( x - 7 = 0 \)[/tex]
[tex]\[ x = 7 \][/tex]
### Final Answer
So, the quadratic equation [tex]\( y = x^2 - 5x - 14 \)[/tex] can be factored as [tex]\( y = (x + 2)(x - 7) \)[/tex], and its zeros/solutions are:
[tex]\[ x = -2 \quad \text{and} \quad x = 7 \][/tex]
[tex]\[ y = x^2 - 5x - 14 \][/tex]
### Step 1: Factoring the quadratic expression
To factor the quadratic expression [tex]\( x^2 - 5x - 14 \)[/tex], we need to find two numbers that multiply to [tex]\(-14\)[/tex] (the constant term) and add up to [tex]\(-5\)[/tex] (the coefficient of [tex]\(x\)[/tex]).
List the pairs of factors of [tex]\(-14\)[/tex]:
- [tex]\((-1, 14)\)[/tex]
- [tex]\((1, -14)\)[/tex]
- [tex]\((2, -7)\)[/tex]
- [tex]\((-2, 7)\)[/tex]
Among these pairs, we need to find the one that adds up to [tex]\(-5\)[/tex]:
- [tex]\((-1) + 14 = 13\)[/tex]
- [tex]\( 1 + (-14) = -13\)[/tex]
- [tex]\( 2 + (-7) = -5\)[/tex]
- [tex]\((-2) + 7 = 5\)[/tex]
The pair [tex]\((2, -7)\)[/tex] adds up to [tex]\(-5\)[/tex], which is what we need.
### Step 2: Writing the equation in factored form
Now that we have found the pair of numbers [tex]\(2\)[/tex] and [tex]\(-7\)[/tex], we write the quadratic equation in its factored form:
[tex]\[ y = (x + 2)(x - 7) \][/tex]
### Step 3: Finding the zeros/solutions of the equation
To find the zeros or [tex]\(x\)[/tex]-intercepts of the equation, we set each factor equal to zero and solve for [tex]\(x\)[/tex]:
1. [tex]\( x + 2 = 0 \)[/tex]
[tex]\[ x = -2 \][/tex]
2. [tex]\( x - 7 = 0 \)[/tex]
[tex]\[ x = 7 \][/tex]
### Final Answer
So, the quadratic equation [tex]\( y = x^2 - 5x - 14 \)[/tex] can be factored as [tex]\( y = (x + 2)(x - 7) \)[/tex], and its zeros/solutions are:
[tex]\[ x = -2 \quad \text{and} \quad x = 7 \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.